Analisis Penguatan Pencegahan Kejahatan (Crime Revention) Melalui Pemolisian Masyarakat (Community Policing) guna Memantapkan Pemeliharaan Keamanan Dan Ketertiban Masyarakat - Hartanto, Dadang; Setyo I, Yustinus; Hamid, Supardi; Yundini, Yundini; Lubis, Rahmadsyah (Universitas Medan Area, 2025)
This study aims to analyze the strengthening of crime prevention through community policing to strengthen the maintenance of public security and order. This research method is This study uses a qualitative approach. A qualitative approach is used to see how policies, programs, and activities reflect the strengthening of crime prevention through community policing in maintaining public security and order. The method used in empirical research. Data collection techniques through document studies and through questionnaires that will be distributed via Google Forms. Next, data analysis is carried out with the stages of data reduction, data presentation, and drawing conclusions. The results of this study found that the jurisdiction of the Riau Regional Police Headquarters has implemented strengthening of crime prevention through community policing by synergizing with various levels of society. All police ranks from the Polsek level to the Polres level have carried out this task. Strengthening crime prevention has been directed at increasing organizational and personnel capacity. The large number of tasks that are not actually the main tasks of functional units still poses an obstacle in the implementation of the implementation of the strengthening results that have been built and worked on. The crime prevention methods used still tend not to fully adapt to the local context and are still strongly oriented towards the methods developed at the Riau Regional Police Headquarters.